Mallory-Weiss Syndrome in Pregnancy - Muhammad Iqbal; Indah Lisfi; Yusrawati yusrawati (Journal of Midwifery, 2022)
Mallory-Weiss syndrome (MWS), which is characterized by bleeding due to mucosal rupture at the gastroesophageal junction, accounts for 1% to 4% of cases with upper gastrointestinal system (GIS) bleeding. Mallory-Weiss tear (MWS) is characterized by longitudinal mucosal lacerations (intra-mural dissection) in the distal esophagus and proximal stomach. These tears usually result from a sudden increase in intra-abdominal pressure. During pregnancy, MWS can develop because of hyperemesis gravidarum in the first trimester, and the volume of bleeding is such that it can be controlled through spontaneous hemostasis. However, reports of third trimester pregnancies complicated by MWS are rare